Sistem Deteksi Kecenderungan Perilaku Agresif Akibat Pengaruh Smartphone Terhadap Psikologis Anak Menggunakan Metode Teorema Bayes dan Certainty Factor - Wahyudi, Wahyudi; Zufria, Ilka; Lubis, Aidil Halim (TIN: Terapan Informatika Nusantara, 2024)
The ease of obtaining information and having complete functions in one hand makes an individual tend not to be separated from a smartphone even for a while because the individual has felt dependent on the smartphone function. Excessive smartphone use in children can have a negative impact on their psychological health, especially in terms of aggressive behavior. Excessive use of smartphones can make children more impulsive, irritable, and prone to aggressive actions. Therefore, a system is needed that can detect the tendency of aggressive behavior in children due to the influence of smartphones to prevent the encouragement of aggressive behavior in children that can make these children capable of committing criminal acts and other negative actions using an expert system. The methods used in this research are the certainty factor method and the Bayes theorem method. Bayes theorem is used to classify and calculate the probability value of a child's tendency to aggressive behavior due to the influence of smartphones. While the certainty factor method is used to determine the confidence value of the probability value obtained using the Bayes theorem. The results of this study illustrate the feasibility of the proposed framework in correctly recognizing the tendency of coercive behavior influenced by smartphone use among children. By utilizing Bayes' theorem and certainty factor, it is expected that this research can help in conducting early detection of the level of aggressive behavior tendencies due to the influence of smartphones. Based on the research that has been done, the system successfully detects 3 (three) levels of tendency, namely low, medium, and high with a percentage of 100% with the results of the Bayes theorem and certainty factor calculations showing in class P3 with a combination of CFcombine(CFold_4,CF_13) has a percentage of 94.17% confidence level and judging from the results of the calculation of the certainty factor combination formula above, it can be concluded that, the child has a tendency to High aggressive behavior.